Outcomes following polypectomy for malignant colorectal polyps are similar to those following surgery in the general population. Issue 1 (26th October 2017) - Lopez, Anthony; Bouvier, Anne-Marie; Jooste, Valérie; Cottet, Vanessa; Romain, Gaëlle; Faivre, Jean; Manfredi, Sylvain; Lepage, Come
Abstract : Objective: Population-based studies on colorectal malignant polyps (MPs) are scarce. The aim of this study was to describe time trends in the incidence of colorectal MPs before and after the introduction of a colorectal mass-screening programmein 2003 and to assess outcomes (survival and recurrence) after endoscopic or surgical resection in patients with MPs. Design: We included 411 patients with MPs diagnosed between 1982 and 2011 in a well-defined population. Age-standardised incidence rates were calculated. Univariate and multivariate 5-year recurrence and net survival analyses were performed according to gross morphology. Results: Age-standardised incidence of MPs in patients aged 50–74 years doubled from 5.4 in 1982–2002 to 10.9 per 100 000 in 2003–2011. Pedunculated MPs were more frequently resected endoscopically (38.2%) than were sessile MPs (19.1%; p <0.001). For patients with pedunculated MPs and a pathological margin ≥1 mm, the 5 -year cumulative recurrence rate did not differ significantly between surgical and endoscopic resection (8.2% and 2.4%, respectively). For patients with sessile MPs, it was 3.0% after firs t-line or second-line surgical resection, 8.6% after endoscopic resection and 17.9% after transanal resection (p=0.016). The recurrence rate decreased dramatically for patients with sessile MPs from 11.3% (1982–2002) to 1.2% (2003–2009) (p=0.010) and remained stable for pedunculated MPs at 4.6% and 6.7%, respectively. Five-year net survival was 81.0% when pathological margins were <1 mm and 95.6% when ≥1 mm (p=0.024). Conclusion: Outcomes following polypectomy in patients with a pathological margin ≥1 mm are similar to those following surgery in the general population. Endoscopic resection needs to be completed by surgery if pathological margins are less than 1 mm.